(untitled) (SCIENCE TIME JOURNAL, 2023)
A lyric poem is rarely more than a page long; an epic might be many volumes lengthy. Meanwhile, dramatic poetry is nearly a hybrid: it conveys a tale but is motivated by emotion. The article discusses the main features of lyrics in English and Uzbek literature. Some types of lyrics are shown and examples have been given from literature.